2010
DOI: 10.1111/j.1365-2494.2010.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing environmental impacts of grassland weed management: can Cirsium arvense be controlled without herbicides?

Abstract: Pywell, R. F., Hayes, M. J., Tallowin, J. B., Walker, K. J., Meek, W. R., Carvell, C., Warman, L. A., Bullock, J. M. (2010). Minimizing environmental impacts of grassland weed management: can Cirsium arvense be controlled without herbicides? Grass and Forage Science, 65 (2), 159-174. IMPF: 01.10Invasion by undesirable plants, such as Cirsium arvense, can constrain attempts to conserve and restore biodiversity in extensively managed temperate grasslands, but control with herbicides can cause environmental harm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 65 publications
(72 reference statements)
0
18
0
1
Order By: Relevance
“…Although domestic grazing is often the causative agent of exotic plant species dominance [31], careful manipulation of timing and intensity of grazing can reduce exotic plant species dominance [32]. Reducing cover of exotic plant species via grazing [3336] can allow rarer plant species a chance to recover [37]. Using grazing to reduce exotic plant species cover does not work in every instance [38], and results will vary depending on the specific grazing regime employed [33].…”
Section: Introductionmentioning
confidence: 99%
“…Although domestic grazing is often the causative agent of exotic plant species dominance [31], careful manipulation of timing and intensity of grazing can reduce exotic plant species dominance [32]. Reducing cover of exotic plant species via grazing [3336] can allow rarer plant species a chance to recover [37]. Using grazing to reduce exotic plant species cover does not work in every instance [38], and results will vary depending on the specific grazing regime employed [33].…”
Section: Introductionmentioning
confidence: 99%
“…Cirsium arvense; De Bruijn and Bork 2006) and Chrysanthemum leucanthemum (Olson et al 1997)). Pywell et al (2010) found the most effective control strategy for Cirsium arvense was low intensity grazing because it maintained a competitive cover of other plant species. Many unpalatable species have life-history stages that are palatable and sensitive to grazing, and the timing of grazing (and the intensity) can be altered to periods when the invasive species is most susceptible (Hartley et al 1984;Thomsen et al 1993;Rinella and Hileman 2009).…”
Section: Control Strategiesmentioning
confidence: 99%
“…As a result, we may have a trade-off between the use of alternative methods of grass control and the development of the forest community under restoration. Nevertheless, green manures reduced spontaneous grass coverage compared to control plots (Favero et al, 2001) and that species richness is reduced in natural regeneration by the use of herbicides (Pywell et al, 2010). Therefore, this dichotomy must be further investigated in order to provide non-chemical methods of grass control in restoration plantings, but with minimum efficiency levels; otherwise, although we may avoid the risks of soil and water contamination associated with herbicide use, we may fail to achieve a well-established native tree community in degraded sites if ineffective alternative methods of grass control are adopted.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, herbicide use, especially of glyphosate, enhances weed control in ecological restoration efforts (Ansley and Castellano, 2006;Carlson and Gorchov, 2004;Cornish and Burgin, 2005). While there is no consensus on the use of herbicides in riparian areas as a safe strategy of weed control in forest restoration, alternative, non-chemical methods of weed control are especially demanded and necessary (Pywell et al, 2010). Following this trend, in Brazil, legal instruments have allowed inter-row cultivation of green manures and short-lived crops with native tree species, such as the São Paulo state environmental office (SMA) resolution nº 8 of 2008.…”
Section: Introductionmentioning
confidence: 99%